2020
DOI: 10.3897/zoologia.37.e52232
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive responses of the male Brandt’s vole, Lasiopodomys brandtii (Rodentia: Cricetidae) to tannic acid

Abstract: Tannins are polyphenols that are present in various plants, and potentially contain antioxidant properties that promote reproduction in animals. This study investigated how tannic acid (TA) affects the reproductive parameters of male Brandt’s voles, Lasiopodomys brandtii (Radde, 1861). Specifically, the anti-oxidative level of serum, autophagy in the testis, and reproductive physiology were assessed in males treated with TA from the pubertal stage. Compared to the control, low dose TA enhanced relative testis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
1
0
0
1
Order By: Relevance
“…There are many behavioral and physiological strategies for small rodents to cope with photoperiod changes in the natural environment. Consistent with the results in hamsters and voles [52][53][54], we also observed that SD photoperiod decreased the body mass and genital organs of Brandt's voles, as compared to LD photoperiod. This strategy is often used by voles to reduce energy consumption in cold winter with low temperature and less food resources [55].…”
Section: Effects Of Photoperiod On Reproductive Physiology and Behaviorsupporting
confidence: 91%
“…There are many behavioral and physiological strategies for small rodents to cope with photoperiod changes in the natural environment. Consistent with the results in hamsters and voles [52][53][54], we also observed that SD photoperiod decreased the body mass and genital organs of Brandt's voles, as compared to LD photoperiod. This strategy is often used by voles to reduce energy consumption in cold winter with low temperature and less food resources [55].…”
Section: Effects Of Photoperiod On Reproductive Physiology and Behaviorsupporting
confidence: 91%
“…Sebagai senyawa antioksidan, tannin dapat mengurangi stress oksidatif dengan menurnkan jumlah ROS dan TNF-α (Wu et al, 2019). Pada testis tannin dapat meningkatkan SOD, GSH-Px, dan CAT yang mengubah senyawa radikal menjadi molekul air yang tidak berbahaya (Dai et al, 2020).…”
Section: Pembahasan Analisis Data Ekspresi Tnf-α Pada Jaringan Testisunclassified